True confessions of a heartless girl - Brooks, Martha, 1944- (Toronto ; Berkeley : Douglas & McIntyre ; [New York] : F arrar, Straus and Giroux, 2002)
The arrival in a small Manitoba town of a troubled seventeen-year-ol d girl forces several residents to finally confront and overcome their own individual tragedies.
"A Goundwood book."
Keywords: Interpersonal relations -- Fiction; Emotional problems -- Fiction; City and town life -- Manitoba -- Fiction; Manitoba -- Fiction